A hospital based study of rickettsial diseases evidenced by Weil Felix test in a tertiary care hospital - Uttam Udayan; Meena Dias; Santosh Machado (Wolters Kluwer Medknow Publications, 2014)
Introduction: Rickettsial infections, one of the re-emerging diseases are increasingly underdiagnosed due to nonspecific symptoms, absence of reliable and affordable diagnostic test and contribute substantially to the acute febrile burden and preventive illness in many populations. A delay in diagnosis and therapy are associated with increased morbidity and mortality. Objectives: To determine and categorize rickettsial disease titers by Weil Felix test, and to know the frequency of rickettsial diseases in febrile patients presenting to a tertiary hospital. Materials and Methods: In a prospective study, a total of 100 samples were tested by Weil Felix test from patients with fever and results were analyzed. Results: Out of 100 samples 64 were positive. Male preponderance was seen. The most common clinical symptom were fever, rash followed by hepatomegaly and splenomegaly. One patient with a high titer of more than 1280 died of encephalitis. Conclusion: In the absence of availability of a good reliable serological or molecular evidence, Weil Felix test can be used in the laboratories mainly due to cost and technical aspects of other reliable tests for diagnosis.